Secondary abdominal ectopic pregnancy - Saire, Laura (2024)
Abdominal ectopic pregnancy is a rare form of ectopic pregnancy. It accounts for1.4% of these cases, with significant morbidity and mortality. We present the caseof a 24-year-old woman with secondary abdominal pregnancy, diagnosed after5 days of unresponsive management of missed abortion. During laparotomy,hemoperitoneum and the presence of a suprauterine chorioamniotic cocoon werefound. Complete removal of the fetus and placenta was performed, preserving theuterus and left adnexa. Despite the rarity, early diagnosis by ultrasound was crucial.Surgical management, often necessary, was challenging, but in early cases such aaours, complete removal can avoid further complications. The importance of earlyrecognition and management of secondary abdominal pregnancy is emphasized.